Gazes in conflict. The penitent sinner between antivoyeurism and the edges of sensuality - Fernández, Natalia (Escritura e Imagen, 2019)
The hagiographical paradigm of the penitent sinner, incarnated by figures such as Saint Mary Magdalene, Saint Mary the Egyptian, Saint Pelagia and Saint Thais, illustrates how the images of sanctity and, specifically, female sanctity, result from a complex system of ways of seeing which goes beyond piety and expresses traditional impulses towards feminity. The contrast sin-holyness shows the crash between two conflictive gazes which reflect a powerful symbolism and, above all, remark the ambivalence of an image, that of the penitent sinner, which reveals itself as an spiritual trompe l’oeil.